Climate propagandas stories of extinction and regeneration - Staal, Jonas 1981- (The MIT Press, 2024)
"Mapping dominant climate propagandas and their worldviews, Staal shows how culture shapes understanding-and misunderstanding-of the world and how to influence a future characterized by regeneration"--
Keywords: Politische Kommunikation; Klimaänderung; Narrativ -- Sozialwissenschaften; Propaganda; Anthropogene Klimaänderung; Umweltkrise; Communication in politics / Comparative method; Climatic changes / Political aspects; Environmentalism / Political aspects; Petroleum industry and trade / Political aspects; Petroleum industry and trade / Social aspects; Extinction (Biology) / Social aspects; Extinction (Biology) / Environmental aspects; Communication politique / Méthode comparative; Climat / Changements / Aspect politique; Environnementalisme / Aspect politique; Pétrole / Industrie et commerce / Aspect politique; Pétrole / Industrie et commerce / Aspect social; Extinction (Biologie) / Aspect social; Extinction (Biologie) / Aspect de l'environnement